2021
DOI: 10.3390/nu13113816
|View full text |Cite
|
Sign up to set email alerts
|

Unique Habitual Food Intakes in the Gut Microbiota Cluster Associated with Type 2 Diabetes Mellitus

Abstract: This cross-sectional study aimed to clarify the characteristic gut microbiota of Japanese patients with type 2 diabetes (T2DM) using t-distributed stochastic neighbor embedding analysis and the k-means method and to clarify the relationship with background data, including dietary habits. The gut microbiota data of 383 patients with T2DM and 114 individuals without T2DM were classified into red, blue, green, and yellow groups. The proportions of patients with T2DM in the red, blue, green, and yellow groups was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Studies with higher precision (larger sample size or smaller standard error) are plotted higher on the axis, while studies with lower precision are plotted lower [ 34 ]. Thus, the study with the highest accuracy in terms of sample size and standard error is the one conducted by Kondo et al [ 48 ], with 497 individuals participating in the study, out of which 383 were diagnosed with T2DM. On the other hand, Van Bommel et al [ 52 ] had the smallest sample size with only 44 T2DM patients, and the research showed that a 12-week treatment of Dapagliflozin or Gliclazide had no effect on the microbial composition.…”
Section: Resultsmentioning
confidence: 99%
“…Studies with higher precision (larger sample size or smaller standard error) are plotted higher on the axis, while studies with lower precision are plotted lower [ 34 ]. Thus, the study with the highest accuracy in terms of sample size and standard error is the one conducted by Kondo et al [ 48 ], with 497 individuals participating in the study, out of which 383 were diagnosed with T2DM. On the other hand, Van Bommel et al [ 52 ] had the smallest sample size with only 44 T2DM patients, and the research showed that a 12-week treatment of Dapagliflozin or Gliclazide had no effect on the microbial composition.…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, type D, the cluster with a high abundance of Bifidobacterium , showed high odds ratios with various disease statuses, including cardiovascular diseases; hepatic diseases; IBD and functional gastrointestinal disorders; psychiatric diseases; and lifestyle-related diseases, such as hypertension, dyslipidemia, hyperuricemia, and diabetes. The functional role of Bifidobacterium in health status is somewhat controversial, as it has been demonstrated that it can be abundant in patients with heart failure [ 21 ], hyperlipidemia, and T2D [ 15 , 22 , 23 ]. Regardless, Bifidobacterium -mediated health benefits are thought to occur as a result of the complex and dynamic interplay among Bifidobacterium , other members of the gut microbiota, and the human host.…”
Section: Discussionmentioning
confidence: 99%
“…To compare the Pakistan gut microbiota with that of other cohorts or populations, we systemically searched for publicly available 16S rRNA gene amplicon (targeting the V3-V4 region) datasets of T2D case-control studies with available metadata or identification of T2D status. Sequences from five published studies were subsequently downloaded from the National Center for Biotechnology Information and the DNA Data Bank of Japan: PRJNA661673 (China), 65 PRJNA766337 (Japan), 66 PRJDB9293 (Indonesia), 67 PRJNA588353 (Sudan), 68 and PRJNA554535 (Pakistan; an independent cohort consisting of participants residing in Islamabad). 15 An endogamous agriculturist Indian cohort of healthy adults (PRJNA399246) was also included, 69 representative of a non-industrialized population from the same geographic region.…”
Section: Methodsmentioning
confidence: 99%